Musicalizando digitalmente: uma alternativa pedagógica em tempos de pandemia - Bezerra, Igor de Tarso Maracajá (2021)
This study aimed to understand how contemporary digital technologies may be worked from a pedagogic action, which encourages musical creation experiences in remote classes with 1st-year elementary school children. Action research was carried out to develop an investigative process that would enable the contribution to personal pedagogical practice and the propagation of reflections about this experience through the dissemination of scientific knowledge. The empirical field was formed by four 1st-year elementary school classes at a private school in the city of João Pessoa – PB, where I have been working as a music teacher for five years. The classes took place remotely during social isolation caused by the COVID-19 pandemic. Despite the growing production in technology and music education, little has been produced for children. A survey of the texts published in the Journal of ABEM 2020 (in the Annals of the Congress of ANPPOM and the Annals of Regional Meetings of ABEM 2020) was performed. Only in the last one studies that had similarities with this theme were found. Additionally, mapping in the Annals of the Regional Meetings of ABEM 2020 was performed to select studies with themes like this research. This mapping allowed to draw an overview of the Music Education production on the theme during the pandemic. Data were analyzed and categorized. Results obtained demonstrated a positive experience of music classes in the virtual environment, although some limitations. The involvement and interest of students in virtual games, used as a pedagogical resource, are noteworthy. This research also produced pedagogical contributions to my experience as a music teacher and may help colleagues who seek to support their practices in academic research.